THE ANALYSIS OF THE SITE OF OMSTU LIBRARY TO COMPLY WITH THE PRINCIPLES OF THE QUALITY OF CULTURE WEB SITES - Mikhaylenko, Illia I.; Mansurova, Svitlana Ye. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The research results of the higher education institution library site for compliance with the quality principles are presented. The directions of improvement of electronic representation of the library in the Internet are planned.